Growth differentiation factor‐15 for prediction of bleeding in cancer patients. (2nd November 2021) - Mulder, Frits I.; Bosch, Floris T. M.; Carrier, Marc; Mallick, Ranjeeta; Middeldorp, Saskia; van Es, Nick; Kamphuisen, Pieter Willem; Wells, Phill S.
Abstract: Background: Growth differentiation factor‐15 (GDF‐15) is a strong predictor for bleeding in patients with atrial fibrillation, but there are no data on cardiovascular outcomes for this biomarker in cancer patients. Bleeding risk assessment is important in cancer patients when considering primary thromboprophylaxis because it is associated with an increased bleeding risk. Objectives: To evaluate GDF‐15 as predictor for bleeding events in cancer patients previously enrolled in the AVERT trial. Patients/Methods: In this trial, 574 participants were randomized to prophylactic apixaban or placebo and followed for 180 days for venous thromboembolism, major bleeding, clinically relevant nonmajor bleeding, and any bleeding. Plasma concentrations of GDF‐15 were measured centrally with the Elecsys GDF‐15 commercial assay kit (Roche Diagnostics GmbH). Results: In apixaban recipients, the area under the receiver operator characteristic curve of GDF‐15 for major bleeding was 0.73 (95% confidence interval [CI], 0.44–1.00). Compared with the lowest GDF‐15 tertile (<1470 ng/L), major bleeding risk was significantly higher in the highest tertile (≥2607 ng/L; hazard ratio [HR] 3.19; 95% CI, 2.41–4.22), also when adjusting for sex, age, antiplatelet use, and gastrointestinal cancer (adjusted HR 2.80; 95% CI, 1.91–4.11). GDF‐15 was also significantly associated with clinically relevant nonmajor bleeding (adjusted HR 1.67; 95% CI, 1.08–2.58) and any bleeding (adjusted HR 2.12; 95% CI, 1.38–3.25). Conclusions: Although hypothesis generating, this is the first study to show that GDF‐15 predicts bleeding in cancer patients receiving thromboprophylaxis.